iGenetics : - Russell, Peter J. (Pearson, 2014)
Pearson With its modern chapter organization and new Focus on Genomics boxes. iGenetics: A Molecular Approach reflects the increasing molecular emphasis in today's experimental study of genes while helping students develop problem-solving skills and an appreciation for classic experiments. Although molecular topics are presented first. instructors can assign the chapters in any sequence.Pedagogical features such as chapter-opening Key Questions and strategically placed Keynotes help students to efficiently master genetic concepts. The enetics Place Companion Website contains interactive iActivities and narrated animations that help students visualize and understand processes and concepts that are illustrated in the text.